2022
DOI: 10.1016/j.ijom.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

CT parameters in pure orbital wall fractures and their relevance in the choice of treatment and patient outcome: a systematic review

Abstract: Computed tomography (CT) is commonly used for the diagnosis, treatment planning, and prognosis of pure orbital fractures of the orbital floor and medial wall. The aim of this study was to systematically review the current literature in order to establish an overview of CT parameters relevant to the choice of treatment and (long-term) clinical outcome for patients treated operatively and conservatively. The PRISMA guidelines were followed. Databases were searched using the terms 'orbital fracture' and 'computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The high incidence of moderate and near-total OBF can be attributed to the high severity of the trauma experienced by our patient population. A systematic review in 2022 studying the use of CT in OBF found that of 31 studies most showed a significant correlation between increasing fracture size and a worse clinical outcome 13 . Hence, we used fracture size as a surrogate for fracture severity in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high incidence of moderate and near-total OBF can be attributed to the high severity of the trauma experienced by our patient population. A systematic review in 2022 studying the use of CT in OBF found that of 31 studies most showed a significant correlation between increasing fracture size and a worse clinical outcome 13 . Hence, we used fracture size as a surrogate for fracture severity in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review in 2022 studying the use of CT in OBF found that of 31 studies most showed a significant correlation between increasing fracture size and a worse clinical outcome. 13 Hence, we used fracture size as a surrogate for fracture severity in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 At the time of this writing, this decision is most often made by the individual clinician based on personal judgment, clinical findings, and radiological imaging. 5 Preoperative computer-assisted planning and intraoperative navigation are becoming increasingly popular for orbital fracture treatment. These technologies had proven to be helpful tools to support the surgeon in treatment in an attempt to optimize orbital reconstruction.…”
mentioning
confidence: 99%
“…At the time of this writing, this decision is most often made by the individual clinician based on personal judgment, clinical findings, and radiological imaging 5 …”
mentioning
confidence: 99%